The influence of transformational leadership and self-efficacy on employee performance with OCB as a mediating variable at PT Star (Semen Bima Corporation) Ajibarang - Dani Aprillia; Hengky Widhiandono; Suyoto Suyoto; Nawalin Nazah (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study uses Organizational Citizenship Behavior (OCB) as a mediating variable to examine the impact of Transformational Leadership and Self-Efficacy on worker performance, at PT. Sinar Tambang Arthalestari (PT. STAR/Semen Bima Corporation) in Ajibarang. The study uses an explanatory research method with a quantitative approach. With a 10% margin of error, the Slovin formula yielded a sample size of 121 out of the 450 employees in the population. Stratified Random Sampling was used as the sampling technique, data data were examined using SmartPLS 4.0 in conjunction with Structural Equation Modeling-Partial Least Squares (SEM-PLS). According to the findings, transformational leadership influences employee performance indirectly, whereas Self-Efficacy exerts consequences that are both direct and indirect. OCB successfully mediates the relationship between these variables: it fully mediates the impact of transformational leadership on worker productivity and somewhat moderates the impact of self-efficacy. These findings demonstrate that enhancing OCB serves as a crucial mechanism for improving employee performance, particularly by bridging the effects of transformational leadership and strengthening the impact of self-efficacy on output. Keywords: Transformational Leadership; Self-Efficacy; Employee Performance; Organizational Citizenship Behavior